Bemused - Rochon, Farrah (Los Angeles Disney Press, 2025)
"The untold origin story of the 5 Muses from Disney's Hercules..."--Provided by publisher.
115455
Keywords: Sisters -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Muses (Greek deities) -- Juvenile fiction; Young adult fiction; Fantasy; Fantasy fiction; Mythological fiction